2021
DOI: 10.1016/j.ins.2020.10.003
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid interval type-2 semi-supervised possibilistic fuzzy c-means clustering and particle swarm optimization for satellite image analysis

Abstract: Although satellite images can provide more information about the Earth's surface in a relatively short time and over a large scale, they are affected by observation conditions (e.g., wind, sun, rain, and humidity) and the accuracy of the image acquisition equipment. The objects on the images are often unclear and uncertain, especially at their borders. The fuzzy clustering technique allows each data pattern to belong to many different clusters through membership function (MF) values that can handle data patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 47 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…Mai et al proposed a hybrid algorithm based on fuzzy c-means clustering and PSO to solve the problem of unclear satellite images at present, and used this algorithm to process the boundaries and fuzzy areas of satellite images. The proposed algorithm's accuracy was 99.2%, which was superior to other comparison algorithms [9]. The automatic recognition system of atmospheric refractive index had low recognition rate.…”
Section: Related Workmentioning
confidence: 84%
See 1 more Smart Citation
“…Mai et al proposed a hybrid algorithm based on fuzzy c-means clustering and PSO to solve the problem of unclear satellite images at present, and used this algorithm to process the boundaries and fuzzy areas of satellite images. The proposed algorithm's accuracy was 99.2%, which was superior to other comparison algorithms [9]. The automatic recognition system of atmospheric refractive index had low recognition rate.…”
Section: Related Workmentioning
confidence: 84%
“…On the other hand, the operating state of energy storage is determined. Then the actual load demand at each time in the system is shown in formula (9).…”
Section: Optimization Of Acm-pso With Individual Adjustment and Cross...mentioning
confidence: 99%
“…Particle swarm optimization (PSO) is a population-based stochastic optimization technique that mimics the swarm behavior of insects, herds, birds, and schools of fish. These groups search for food in a cooperative way, and each member of the group constantly changes its search mode by learning its own experience and that of other members [21][22][23]. Take the birds as an example.…”
Section: Evaluation Model Of Youth Basketballmentioning
confidence: 99%
“…Another recent study on this area is shown in [24], where the authors presented a hybrid semi-supervised interval type-2 possibilistic fuzzy c-means clustering and particle swarm optimization for optimizing results in satellite image analysis.…”
Section: Literature Reviewmentioning
confidence: 99%